A Semianalytical Model for Multiple-Fractured Horizontal Wells with SRV in Tight Oil Reservoirs. (29th November 2017) - Wang, Jiahang; Wang, Xiaodong; Dong, Wenxiu
Abstract : The paper developed a new semianalytical model for multiple-fractured horizontal wells (MFHWs) with stimulated reservoir volume (SRV) in tight oil reservoirs by combining source function theory with boundary element idea. The model is first validated by both analytical and numerical model. Then new type curves are established. Finally, the effects of SRV shape, SRV size, SRV permeability, and parameters of hydraulic fractures are discussed. Results show that SRV has great influence on the pressure response of MFHWs; the parameters of fractures, such as fracture distribution, length, and conductivity, also can affect the transient pressure of MFHWs. One novelty of this model is to consider the nonlinear flow around hydraulic fracture tips. The other novelty is the ability to model the shape of the SRV, production behavior of different fractures, and interfaces. Compared to numerical and analytic methods, this model can not only reduce extensive computing processing but also show high accuracy.